Debates and training in gender violence: challenging professional practices in the Justice of Córdoba, Argentina - Beatriz Rotondi, Gabriela (2019)
The article reconstructs experiences related to processes of debates and training in gender violence carried out with professionals from different disciplines who work in public areas and institutions of the local environment in the field of justice. In this journey, what is intended to highlight is the necessary involvement of the University both in the study and research of social problems and in its approach to starting, in this case, training spaces with professionals who carry out their practices in the field of intervention. The experiences collected here are developed from the university field from the Faculty of Social Sciences, in particular from the Degree in Social Work of the National University of Cordoba. In these instances knowledge is built from the exchange of knowledge, the practices carried out by the professionals are recognized, the interventions are recreated and collectively influenced on policies related to gender violence.